Ultrasonography of articular and periarticular structures as a relapse predictor in patients with clinically remitted rheumatoid arthritis - Mehdi Karami; Zohre Mohammadzadeh; Shadi Ebrahimian; Maryam Moradi; Sayedbonakdar Zahra (Indian Journal of Rheumatology)
Introduction: Rheumatoid arthritis (RA) is an autoimmune disease causing mortality and morbidity among patients. The goal of RA treatment is remission and prevention of joint degeneration. Remission is diagnosed by physical examinations and laboratory markers. Due to the high rate of relapse, it appears that physical examination is not a sensitive method in detecting active and remitted RA patients. The aim of this study is to find whether ultrasonography (US) is an appropriate method in detecting active RA patients and estimating the relapse rate. Methods: Seventy clinically remitted RA patients were enrolled based on the Disease Activity Score in 28 joints. They underwent US to examine the presence of synovitis, tendinitis, tenosynovitis, and bursitis and were followed for 6 months regarding the relapse rate. Moreover, the predictive value of US was measured. SPSS was used for analyzing data. Results: According to the US findings, 27.1% of the clinically remitted patients had signs of active synovitis, whereas 15.7% of them showed signs of tenosynovitis, tendinitis, or bursitis. In addition, relapse was observed in 12.9% of the patients with clinical remission and was significantly higher in patients with signs of active synovitis (P < 0.05). The results also revealed that the prognostic values of US for estimating the relapse rate were 77.7% and 70.0% in terms of sensitivity and specificity, respectively. Conclusions: US is capable of detecting active synovitis among patients with clinically remitted RA and also predicts those with a higher risk of relapse within 6 months. It is also useful in identifying people with active RA, whose clinical symptoms indicate remission of the disease. Involvement of periarticular structures including tenosynovitis, tendinitis, or bursitis cannot independently predict relapse in patients with RA.